2021
DOI: 10.3389/fcimb.2021.716809
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Human Peripheral Blood Mononuclear Cells Stimulated by Mycobacterium tuberculosis PPE57 Identifies Characteristic Genes Associated With Type I Interferon Signaling

Abstract: Proline-glutamic acid (PE)- and proline-proline-glutamic acid (PPE)-containing proteins are exclusive to Mycobacterium tuberculosis (MTB), the leading cause of tuberculosis (TB). In this study, we performed global transcriptome sequencing (RNA-Seq) on PPE57-stimulated peripheral blood mononuclear cells (PBMCs) and control samples to quantitatively measure the expression level of key transcripts of interest. A total of 1367 differentially expressed genes (DEGs) were observed in response to a 6 h exposure to PPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…The connections between genes may indicate physical interaction between some of the encoded proteins, or that the proteins jointly contribute to a shared function [ 39 ]. Proteins IFIT2 and IFIT3 centered in the network are IFN-α/β induced proteins and highly expressed during cell-intrinsic immune response to Mtb infection [ 40 ]. Further, we observed that STAT1 forms associations with many proteins in the network ( n = 17); STAT1 is known to be an immunoregulatory factor that regulates both IFN-α/β and IFN-γ -mediated responses [ 7 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The connections between genes may indicate physical interaction between some of the encoded proteins, or that the proteins jointly contribute to a shared function [ 39 ]. Proteins IFIT2 and IFIT3 centered in the network are IFN-α/β induced proteins and highly expressed during cell-intrinsic immune response to Mtb infection [ 40 ]. Further, we observed that STAT1 forms associations with many proteins in the network ( n = 17); STAT1 is known to be an immunoregulatory factor that regulates both IFN-α/β and IFN-γ -mediated responses [ 7 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“… 32 In addition, overexpression of MX1 was identified in human peripheral blood mononuclear cells stimulated with M. tb PPE57. 33 IFIH1 is a novel regulator for promoting M1 macrophage polarization. 34 STAT1 is a member of the STAT protein family and a key component that mediates interferon signaling.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Similar to MX1, overexpressed IRF7 was also detected in human peripheral blood mononuclear cells stimulated by M. tb PPE57. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pink module, we identified several critical functional terms related to inflammation and immune response, such as “NF-kappa B signaling pathway,” “TNF signaling pathway,” and “B cell receptor signaling pathway” in the tan module, as well as terms such as “cytokine-mediated signaling pathway (GO:0019221),” “negative regulation of programmed cell death (GO:0043069),” “toll-like receptor 2 signaling pathway (GO:0034134),” and “negative regulation of epithelial cell apoptotic process (GO:1904036)” in the salmon module. Moreover, several hub-central genes/TFs of the tan module such as CD40 ( Khan et al, 2016 ), CD274 ( Petrilli et al, 2020 ), CTNNB1 ( Subuddhi et al, 2020 ), IKBKE ( Killick et al, 2014 ), IL23R ( Jiang et al, 2015 ), MAPK7 ( María Irene et al, 2021 ), TRAF2 ( Killick et al, 2014 ), NFKB1 ( Meade et al, 2007 ), NFKB2 ( Magee et al, 2012 ), and STAT6 ( Cronan et al, 2021 ), as well as hub-central genes of the salmon module, such as CASP4 ( Malone et al, 2018 ), DHX58 ( Nalpas et al, 2015 ), IL10 ( Wang et al, 2011 ), MX1 , MX2 , IFIT2 ( Yi et al, 2021 ), RIPK2 ( Widdison et al, 2011 ), TRAF1 ( Li H. et al, 2017 ), and USP18 ( Carranza et al, 2020 ), have been reported to be involved in the host immunity and M. bovis pathogenesis. The NFKB1 hub-central TF is a major mediator of the proinflammatory immune response that stimulates the transcription of proinflammatory cytokines and chemokines and has shown a significant reduction in the response to M. bovis infection ( Meade et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%